Abdominal Computed Tomography Utilization and 30‐day Revisitation in Emergency Department Patients Presenting With Abdominal Pain. (25th June 2015) - Patterson, Brian W.; Venkatesh, Arjun K.; AlKhawam, Lora; Pang, Peter S.; Carpenter, Christopher R.
Abstract Objectives The objective was to explore which patient characteristics are associated with repeat emergency department (ED) visitation within 30 days of ED discharge for patients presenting with abdominal pain. Methods A retrospective, observational study was conducted at a single, academic, urban ED with over 85, 000 annual visits. A consecutive sample of adult patients with a chief complaint of abdominal pain from January 2010 through December 2010 who were discharged following ED evaluation were included in the analysis. A logistic regression model was used to determine which patient‐level factors, including computed tomography (CT) utilization, were associated with the primary outcome of ED revisit within 30 days. Results Of 80, 619 total ED patient visits during the study period, 3, 928 ED discharges with a chief complaint of abdominal pain were included. A total of 487 (12.4%) patients revisited the ED within 30 days. No deaths were recorded. CT imaging was associated with a lower 30‐day revisit rate (odds ratio [OR] = 0.69, 95% confidence interval [CI] = 0.55 to 0.87) after controlling for multiple other patient‐level factors associated with revisits. Increasing age (OR = 1.01, 95% CI = 1.00 to 1.02), increasing triage pain scores (OR = 1.13, 95% CI = 1.08 to 1.18), elevated triage heart rate (OR = 1.42, 95% CI = 1.07 to 1.89), low sodium levels (OR = 1.56, 95% CI = 1.07 to 2.23), and anemia (OR = 1.42, 95% CI = 1.04 to 1.95) were all associated with increased rate of return. Conclusions Performance of an abdominal CT was associated with fewer 30‐day revisits, suggesting that future measures of "imaging appropriateness" and "ED overuse" consider downstream utilization of health care resources in addition to the index visit.